The Role of the Giri Mulya Learning Community in Empowering Women Through Entrepreneurship Learning - Susilo, Heryanto; Rasyad, Ach.; Zulkarnain; Hardika (Journal of Population and Social Studies [JPSS], 2024)
Munggugebang Village, Beijing District, Gresik Regency, East Java, Indonesia, is a village where most people work as farmers. Much potential still needs to be maximized for village development. Seeing this potential, the Giri Mulya learning community aims to provide education related to entrepreneurship to help develop village potential targeting women. These women are expected to be able to support the achievement of a program. In carrying out a program, there are inhibiting and supporting factors. This research aims to determine the processes and factors that support and hinder women’s empowerment in entrepreneurial learning in villages, which are learning communities. This research uses a qualitative approach with a case study method. The informants were learning community organizers, facilitators, village communities, and community leaders. Data was collected using observation techniques, in-depth interviews, and documentation studies. Data analysis was done using Miles et al. (2018) interactive model. The research results show that entrepreneurship learning for women in Munggugebang Village can have a positive impact on their ability to cultivate village potential and participate actively in facilitating village Micro, Small, and Medium Enterprises (MSMEs) by making burlap sacks, processing duck eggs into salted eggs, and several other activities.